Eduwisata Art-Edu-Tech : Model Pengembangan Kawasan Wisata Air Terjun Candi Kuning, Silangjana, Buleleng - Ni Putu Laras Purnamasari; I Wayan Suanda; I Kadek Juni Arta; A.A Istri Agung Mutiara Mahayeni; I Made Arsa Sanjaya Putra (Pusat Riset dan Inovasi Nasional, 2026)
Silangjana Village in Buleleng, Bali, has natural tourism potential, one of which is the Candi Kuning Waterfall. The potential of Silangjana Village has not been balanced by structured educational tourism, village economic institutions, and low digital literacy and human resource capacity. The Impact Student Executive Board (BEM Berdampak) program has the main objective of increasing the capacity and empowerment of two target partners, namely the Lila Dharma Kerti Tourism Awareness Group (Pokdarwis) and the Dharma Kerthi Honey Bee Farmer Group, through the implementation of the innovative Eco-Art-Tech model. This model integrates environmental sustainability, namely Eco which refers to modern Trigona bee cultivation, Art which targets the creative economy with a program to recycle plastic waste into souvenirs, and Tech for digital systems supporting tourist attractions. The program's implementation methods include outreach, technical training, mentoring, and evaluation. Initial results show a significant increase in the knowledge and skills of Tourism Awareness Group (Pokdarwis) partners regarding source-based plastic waste management, as well as their ability to create various souvenir products such as fans, wallets, and key chains, to support tourism promotion. The Bee Farmers Group also experienced an increase in knowledge regarding modern Trigona honey cultivation techniques, and even achieved an effective and hygienic honey harvest. This program supports the SDGs and community economic independence.